DAMPAK DAN RESIKO PERPINDAHAN IBU KOTA TERHADAP EKONOMI DI INDONESIA - Reni Ria Armayani Hasibuan; Siti Aisa (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2020)
President Jokowi has announced plans to move the country's capital city (IKN) to East Kalimantan Province. This IKN transfer must be carefully planned because there are potential positive impacts as well as risks. The background of moving the IKN is that the burden on DKI Jakarta as the center of government and business center is too high. The transfer of IKN also aims to reduce economic inequality between Java and outside Java. Therefore, this paper will analyze the economic impact along with the risks of moving the IKN that the government must anticipate. In the economic aspect, there is potential for an increase in GDP accompanied by a controlled inflation rate. However, there is a risk of financing originating from the State Budget, BUMN, business entities and the private sector. The government must pay attention to the cooperation scheme with these parties considering the construction of a 'new city' and its infrastructure carries a high risk. In addition, there is potential for more than expected inflation stemming from the increase in land prices. The DPR RI monitors the progress of the IKN transfer plan through the supervisory function mechanism.